Les sanctions économiques et les petits États : Le cas de la « punition » du Vietnam par le Canada - Nossal, Kim (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1987)
The purpose of this paper is to examine this assumption — that size and power makes a difference to the definition of the utility of economic sanctions. It examines as a case study the employment of Canadian sanctions against Vietnam. The paper will argue that this case demonstrates that, for a non-great power, the utility of economic sanctions is rarely limited to the usual objectives attributed to, and derived from the experience of, great power s: exercising power against the 'targef' state or signalling one's power to other states in the system. Instead, it will argue that for a middle power like Canada, the use of sanctions becomes inextricably bound to foreign policy-maker s perceptions of the politics of coalition obligations ; and of the imperatives and constraints of bilateral relations with the major power s.